A bibliometric analysis of the Role of Families on the Importance of Educational Strategies in Addressing Racism and Discrimination in Society - Ginting, Dafid (West Science Social and Humanities Studies, 2024)
This bibliometric analysis delves into the extensive literature exploring the intricate relationship between families, educational strategies, racism, and discrimination. Utilizing databases such as PubMed, Scopus, and Web of Science, the study systematically identifies 860 relevant papers published between 1976 and 2023. Through a structured search strategy and the application of bibliometric tools like VOSviewer, the analysis maps the intellectual structure, key themes, and research trends. The identified clusters, including themes like racial discrimination, socialization, and adolescent development, reveal the dynamic evolution of research in this field. High citation counts for influential literature, such as "American apartheid: segregation and the making of the underclass," and "Whose culture has capital? A critical race theory discussion of community cultural wealth," emphasize the lasting impact of seminal works. The study contributes to evidence-based policymaking, providing insights for addressing societal issues and guiding future research aimed at fostering a more inclusive and equitable society.